2005
DOI: 10.1002/ajpa.20232
|View full text |Cite
|
Sign up to set email alerts
|

Linear enamel hypoplasias as indicators of systemic physiological stress: Evidence from two known age‐at‐death and sex populations from postmedieval London

Abstract: Enamel hypoplasias are useful indicators of systemic growth disturbances during childhood, and are routinely used to investigate patterns of morbidity and mortality in past populations. This study examined the pattern of linear enamel hypoplasias in two different burial populations from 18th and 19th Century church crypts in London. Linear enamel hypoplasias on the permanent dentitions of individuals from the crypt of Christ Church, Spitalfields, were compared to enamel defects on the teeth of individuals from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
152
2
11

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(176 citation statements)
references
References 46 publications
4
152
2
11
Order By: Relevance
“…King et al (2005) revealed that younger individuals of a skeletal series, or individuals who died earlier in life, had an earlier first incidence of LEH than the older individuals. Although we examined the relationship between the first occurrence of LEH and individual ages in the Kumejima series, no positive correlations were found; however, the fact that the younger and female individuals tended to be more affected in the Kumejima series indicates that females (when they were children) experienced greater physiological stress than males, and that individuals that died younger tended to have been exposed to greater stress during childhood, as reported in the medieval Danish village of Tirup (Boldsen, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…King et al (2005) revealed that younger individuals of a skeletal series, or individuals who died earlier in life, had an earlier first incidence of LEH than the older individuals. Although we examined the relationship between the first occurrence of LEH and individual ages in the Kumejima series, no positive correlations were found; however, the fact that the younger and female individuals tended to be more affected in the Kumejima series indicates that females (when they were children) experienced greater physiological stress than males, and that individuals that died younger tended to have been exposed to greater stress during childhood, as reported in the medieval Danish village of Tirup (Boldsen, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Because ameloblasts are lost with tooth eruption, enamel is not capable of further growth or remodeling, i.e. LEH provides a means by which growth disturbance during early childhood can be examined from the permanent teeth of adults (King et al, 2005). Therefore, many authors have investigated the prevalence and timing of LEH in a range of prehistoric cranial series (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, women usually show more severe nutritional stress markers, such as frequent enamel hypoplasias, less intervals between defects and more frequent tooth growth disruptions (King et al, 2005).…”
Section: Key Factors Related To Caries Prevalence In Human Populationmentioning
confidence: 99%
“…However, an investigation of sex differences in LEH for a particular period in Japan has not previously been reported. Research in other countries has produced contradictory results: higher prevalence in males (Van Gerven, et al, 1990;Saunders and Keenleyside, 1999;Palubeckaite, et al, 2002), higher prevalence in females (May et al, 1993;Slaus, 2000;King, et al, 2005), and no significant differences between the sexes (Goodman et al, 1980;Lanphear, 1990;Duray, 1996;Malville, 1997;Lovell and Whyte, 1999;Slaus, 2008).…”
Section: Sex Differencesmentioning
confidence: 99%